STT를 활용한 수업에서 학습자의 인지 능력의 효과 분석 - 강현민(HyunMin Kang); 한선관(SunKwan Han) (한국컴퓨터정보학회논문지, 2024)
본 연구는 인공지능을 활용한 수업이 항공전문학교 학생의 인지적으로 미치는 영향을 검증하였다. 먼저 프레젠테이션을 활용한 수업에서 전통적인 멀티미디어 자료 기반의 수업과Speech-to-text(STT)기반의 인공지능 자료로 구성된 수업을 개발하였다. A 항공 전문 교육기관의학생 133명이 두 가지 유형의 수업에 참여하였다. 수업 전후에 학생들의 인지 부하와 Mind Wandering을 측정하였고, 성취도평가를 실시하였다. 검사의 분석 결과, 외재적 인지 부하는 감소하였고 콘텐츠 집중도가 높아졌으며 성취도가 향상됨을 확인하였다. 향후 기술을 지도하는 학교에서 인공지능 기반의 STT수업이 많이 활용되기를 기대한다. This research studied the cognitive impact of classes using artificial intelligence on aviation technical school students. First, we developed a class consisting of a class based on traditional presentation materials and a class composed of speech-to-text (STT)-based artificial intelligence materials. A 133 students from an aviation education institution participated in two types of classes. We measured students' cognitive load and Mind Wandering test results before and after class, and conducted an achievement evaluation. As a result of the test analysis, we confirmed that extraneous cognitive load was reduced, content concentration increased, and achievement improved. In the future, we hope that AI-based STT classes will be widely used in schools that teach technology. KCI Citation Count: 0